Localization of Myosin 1b to Actin Protrusions Requires Phosphoinositide Binding - Komaba, Shigeru (American Society for Biochemistry and Molecular Biology, 2010)
Myosin 1b (Myo1b), a class I myosin, is a widely expressed, single-headed, actin-associated molecular motor. Transient kinetic and single-molecule studies indicate that it is kinetically slow and responds to tension. Localization and subcellular fractionation studies indicate that Myo1b associates with the plasma membrane and certain subcellular organelles such as endosomes and lysosomes. Whether Myo1b directly associates with membranes is unknown. We demonstrate here that full-length rat Myo1b binds specifically and with high affinity to phosphatidylinositol 4,5-bisphosphate (PIP(2)) and phosphatidylinositol 3,4,5-triphosphate (PIP(3)), two phosphoinositides that play important roles in cell signaling. Binding is not Ca(2+)-dependent and does not involve the calmodulin-binding IQ region in the neck domain of Myo1b. Furthermore, the binding site is contained entirely within the C-terminal tail region, which contains a putative pleckstrin homology domain. Single mutations in the putative pleckstrin homology domain abolish binding of the tail domain of Myo1b to PIP(2) and PIP(3) in vitro. These same mutations alter the distribution of Myc-tagged Myo1b at membrane protrusions in HeLa cells where PIP(2) localizes. In addition, we found that motor activity is required for Myo1b localization in filopodia. These results suggest that binding of Myo1b to phosphoinositides plays an important role in vivo by regulating localization to actin-enriched membrane projections.